Sertoli Cell-Only Syndrome with Normal Karyotype - AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; SOUMANOU, FOUAD; Hodonou, Fred; Djengue, Euodias (My University, 2018)
Sertoli cell-only syndrome is usually associated with micro deletion Y chromosome. We reported rare case in the 37years-old-man married 10 years ago. A left varicocele was associated with this syndrome. No micro deletion Y chromosome was noted. Left varicocelectomy has been perfomed.
Keywords: Azoospermia; Sertoli Cell-Only Syndrome; Testicular Biopsy.